Secure obfuscation for encrypted threshold signatures - Yahong LI; Caifen WANG; Yulei ZHANG; Xiaodong YANG; Haiyan HUANG (Tongxin xuebao)
Aiming at the key leakage security problem of the threshold signature,an encrypted threshold signature functionality was firstly proposed and securely obfuscated.The output of obfuscated circuit could be implemented by any third party without revealing the private key of threshold signature.Secondly,the security models of encrypted threshold signature functionality and the obfuscator were defined,such as the existential unforgeablity and the average case virtual black box property,and its correctness and security were proved.The analyses of theory and simulation experiment show that the obfuscation for encrypted threshold signature has feasibility.